Reproductive pattern of dog-faced fruit bat Cynopterus brachyotis muller in Bintulu, Sarawak, Malaysia - Ibrahim, Azema (2013)
Reproductive period is a critical phase for most living organisms including bats. However the influence of environmental condition on the reproductive patterns of Chiroptera in Malaysia is not well studied. The development in industries, urbanisation, animal husbandry, agriculture, and the fragmentation and isolation of natural habitats are currently affect population of bats. If there is no restriction to these man-made disturbances, it will lead to the extinction of bat populations due to loss of habitat, pollution, decreasing food resources, deliberate killing, and loss of genetic diversity. Therefore, the objective is to determine the reproductive status of C. brachyotis, to determine the effects of environmental factors on C. brachyotis reproduction and to investigate the synchronisation of reproductive patterns between male and female C. brachyotis. A study on the reproductive patterns of dog-faced fruit bat, C. brachyotis was conducted at Universiti Putra Malaysia Bintulu Campus, Sarawak (UPMBC). Bats were captured in the abandoned oil palm plantation, Planted Forest which is a cultivated forest since 1990, Nirwana Natural Forest which is a secondary forest and was logged 18 years ago and Forestry Park which is also a secondary forest, using mist-nets for a period of 14 months from January 2009 to February 2010. The reproductive status was determined based on morphology of the bats. Five (I-Minor testes enlargement, no epididymal distention, II-Testes at or near maximal enlargement, no epididymal distention, III-Testes regressed, cauda epididymal distented, IV-Testes not regressed, cauda epididymal distented and V-No testiscular or epididymal enlargement) and four categories (I-Possibility pregnant, II-Lactating, III-Post-lactating and IV-Not reproductively active) of reproductive status were categorized for male and female C. brachyotis respectively. Bintulu climatic data were obtained from Kuching Meteorology Station, Sarawak. Assessment of fruit availability was done by casual observation. Bats reproduced at all time of the year and the peak periods were associated with the rainy seasons. The first peak of reproduction (pregnancy and lactation) occurred in January to April 2009 and second peak in June to November 2009. The highest frequency of pregnancy and lactation female coincided with the fruit abundance and the rainy season. The results indicated that C. brachyotis performed a non-seasonal reproductive pattern. The knowledge on C. brachyotis reproductive biology can be used in the management and conservation of other threatened bat species.